Increased Mean Platelet Volume (MPV) in Patients with ST Elevation Myocardial Infarction (STEMI) Compared to Non-ST Elevation Myocardial Infarction (NSTEMI) Patients - Tri Ratnaningsih; Istiqomah Istiqomah (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2020)
Platelets are known to have a role major in the pathogenesis of atherothrombosis. More giant and hyperreactive platelets accelerate the formation of an intracoronary thrombus. An increased MPV as an indicator of larger and more reactive platelets represents a risk factor for overall vascular mortality, including myocardial infarction. This study aimed to identify the increase of Mean Platelet Volume in Patients with Acute Coronary Syndromes, especially in ST-elevation myocardial infarction and Non-ST-elevation myocardial infarction. Thus this parameter can be used as consideration for diagnosis and treatment decisions. This research is an analytic observational with a cross-sectional method. The subjects were patients with STEMI and NSTEMI who were hospitalized in ICCU Dr.Sardjito Hospital Yogyakarta. Thirty-four subjects STEMI and NSTEMI patients at Dr. Sardjito Hospital, consisting of 28 males (82,35%) and six women (17,65%) with a mean age of 55,5 ± 10,3 years. The results showed that MPV in AMI was higher in patients with STEMI than NSTEMI, but this difference is not significant (p = 0,091). This study concludes that MPV to be higher in patients with STEMI compared to NSTEMI. MPV may be used as a marker of myocardial infarction in clinically appropriate situations.